2014
DOI: 10.1016/j.proche.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric Determination of Aflatoxin B1

Abstract: For the first time the possibility of voltammetry used for the determination of aflatoxin B1 on a glassy carbon electrode was shown. The effect of pH of a supporting electrolyte on the analytical signal of aflatoxin B1 has been investigated and it was shown that there is a more pronounced peak with a maximum current at pH of 5.33. The most favorable supporting electrolyte for a linear range of detectable concentrations of aflatoxin B1 – 0.1 M (NH[4])[2]SO[4] was determined. The results of research on the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Studies on the effect of the background electrolyte composition on the analytical signals of aflatoxins В 1 and М 1 on a glassy-carbon electrode under working conditions previously developed for the determination of aflatoxin В 1 were conducted [ 24 ]. Experiments on the choice of the background electrolyte showed that the value of the analytical signal aflatoxin M 1 on background electrolytes: 0.1 M Na 3 PO 4 , 0.1 M Na 2 HPO 4 , 0.1 M K 2 HPO 4 , and 0.1 M ZnSO 4 , was found to be low, and it was high on background electrolytes: 0.1 M (NH 4 ) 2 SO 4 and 0.1 M Li 2 CO 3 ; the maximum current of its electric oxidation was obtained against the background of 0.1 M C 6 H 5 O 7 (NH 4 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the effect of the background electrolyte composition on the analytical signals of aflatoxins В 1 and М 1 on a glassy-carbon electrode under working conditions previously developed for the determination of aflatoxin В 1 were conducted [ 24 ]. Experiments on the choice of the background electrolyte showed that the value of the analytical signal aflatoxin M 1 on background electrolytes: 0.1 M Na 3 PO 4 , 0.1 M Na 2 HPO 4 , 0.1 M K 2 HPO 4 , and 0.1 M ZnSO 4 , was found to be low, and it was high on background electrolytes: 0.1 M (NH 4 ) 2 SO 4 and 0.1 M Li 2 CO 3 ; the maximum current of its electric oxidation was obtained against the background of 0.1 M C 6 H 5 O 7 (NH 4 ) 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxins are absorbed in the gastrointestinal tract but not been biotransformed in the liver can also be excreted (Scaglioni et al, 2014). Thus aflatoxin can accumulate through the food chain posing a serious health concern to both humans and animals (Otim et al, 2005;Gavrilova et al, 2014;Patel et al, 2015). However, according to the survey conducted throughout North western Italy between 2012 and 2014, the overall AFM contamination rate was 2.2% (36 samples out of 1668 samples) and less than 1% of milk samples were non-compliant with EU limits (Bellio et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Aflatoxins are potent toxic, carcinogenic, mutagenic and immunosuppressive agents produced as secondary metabolites by Aspergillus flavus and Aspergillus parsisticus on a variety of food products (Ozay et al, 2008). The levels of aflatoxins contamination is a cumulative and therefore are associated with acute and chronic toxicities to both humans and animals (Otim et al, 2005;Gavrilova et al, 2014;Patel et al, 2015;El Zubeir, 2023). The higher occurrence of aflatoxin M1 in raw and processed milk samples might have a negative impact on public health, especially infants and children who consumed large amount of fluid milk (Fadlalla et al, 2020;Yousof and El Zubeir, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, mycotoxin contamination resistor difficulties are mainly applicable and resolved not only within specific states, but also worldwide, under the support of the Food and Agriculture Organization and World Health Organization [1]. Aflatoxins are secondary toxic metabolites produced by numerous fungi such as Aspergillus flavus, Aspergillus parasiticus, Aspergillus nomius, and Aspergillus pseudotamarii [2]. Aflatoxin B1 (AFA−B1) is also known as 2,3,6a R ,9a S ‐tetrahydro‐4‐methoxy‐1 H ,11 H ‐cyclopenta[c]furo[3′,2′:4,5]furo[2,3 h]benzopyran‐1,11‐dione (Figure 1).…”
Section: Introductionmentioning
confidence: 99%